Analysis of Deviant Behavior of Class X Students at SMA Muhammadiyah Maumere - Kudara, Andiriani; Kepalet, Petrus; Natsir, H. Rodja Abdul (EDUCTUM: Journal Research, 2022)
Deviant behavior of adolescents or students can also be referred to as juvenile delinquency, which is an act that violates norms, rules or laws in society that is carried out at a young age or during the transition between childhood and adulthood. Juvenile delinquency in the study of social problems can be categorized into deviant behavior. deviant behavior that often occurs in class X students is individual deviation such as stubbornness including dating at school, being late), skipping school, skipping class and smoking in the school toilet. The research results obtained from several informants that there are several causal factors that influence deviant behavior by students due to several factors including "School, Family and Community Environment". Social Impact of Deviant Behavior "Here it is explained that the social impact of students' deviant behavior will first affect the surrounding community. Where people will see deviant behavior by students, they will definitely imitate what is done in terms of deviance. And the second is lazy, why is laziness said to be a social impact because this laziness will become a habit if at school students do not do their assignments then this lazy habit will bottom out of the school environment. Obstacles in Preventing Deviant Behavior. "The first obstacle in preventing deviant behavior is not fully controlling students. This deviant behavior occurs not only at school but outside of school also often occurs, causing deviant behavior. The school community's efforts to deal with deviant behavior are carried out by school members by holding spiritual activities, such as congregational prayers and reciting the Koran at mosques for the Muslim religion, while Catholic students pray together in class with Catholic Religious Education teachers before going home from school.